Layered Double Hydroxides (LDH) as Delivery Vehicles of a Chimeric Protein Carrying Epitopes from the Porcine Reproductive and Respiratory Syndrome Virus - María José Alonso-Cerda; Mariano J. García-Soto; Arleth Miranda-López; René Segura-Velázquez; José Ivan Sánchez-Betancourt; Omar González-Ortega; Sergio Rosales-Mendoza (MDPI AG, 2024)
The Porcine Reproductive and Respiratory Syndrome Virus (PRRSV) causes reproductive failure and respiratory symptoms, leading to huge economic losses for the pig farming industry. Although several vaccines against PRRSV are available in the market; they show an overall low efficacy, and several countries have the need for vaccines covering the local, circulating variants. This project aims at developing a new chimeric antigen targeting specific epitopes from PRRSV and evaluating two test adjuvants to formulate a vaccine candidate. The test antigen was called LTB-PRRSV, which was produced recombinantly in Escherichia coli and consisted of the heat labile enterotoxin B subunit from E. coli (LTB) and four epitopes from PRRSV. LTB-PRRSV was rescued as inclusion bodies and methods for its solubilization, IMAC-based purification, and refolding were standardized, leading to mean yields of 18 mg of pure protein per liter culture. Layered double hydroxides (LDH) have been used as vaccine adjuvants given their biocompatibility, low cost, and positive surface charge that allows an efficient adsorption of negatively charged biomolecules. Therefore, LDH were selected as delivery vehicles of LTB-PRRSV. Pure LTB-PRRSV was adsorbed onto LDH by incubation at different LDH:LTB-PRRSV mass ratios (1:0.25, 1:0.5, 1:1, and 1:2) and at pH 9.5. The best adsorption occurred with a 1:2 mass ratio, and in a sucrose-tween solution. The conjugates obtained had a polydispersity index of 0.26, a hydrodynamic diameter of 192 nm, and a final antigen concentration of 64.2 μg/mL. An immunogenicity assessment was performed by injecting mice with LDH:LTB-PRRSV, Alum/LTB-PRRSV, or LTB-PRRSV in a scheme comprising three immunizations at two-week intervals and two dose levels (1 and 5 μg). LTB-PRRSV was capable of inducing strong humoral responses, which lasted for a longer period when LDH was used as the delivery vehicle/adjuvant. The potential of LDH to serve as an attractive carrier for veterinary vaccines is discussed.